THE EFFICACIES OF BANANA STEM EXTRACT AS A CANDIDATE OF COCCIDIOSTAT AGAINST RABBIT EIMERIA STIEDAIO OCYSTS: AN IN VITRO ANALYSIS - Indrasanti, Diana; Indradji, Mohandas; Hastuti, Sri; Wihadmadyatami, Hevi; Ismoyowati, Ismoyowati (ANIMAL PRODUCTION, 2015)
The objective of this research was to investigatethe ability of banana stem (Musa paradisiaca) to inhibitsporulation of Eimeria stiedaioocystsderived fromrabbit by in vitroanalysis.Analyze the active substance proximate analysis and active substancesin this research were performed too. Banana stem extract were used in this experiment andsulfaquinoxalline(Coxy ®)was run as acontrol. The Eimeria stiedaioocystswere incubated prior the presence of  different concentration from banana stem extract  0%, 1%, 2%, 4%, 8%for 1, 2 and 3 daysat 26°C. In addition,Factorial patterned Completely Randomized Design (CRD) with five replicates wasapplied on the experiment. Result analysis was performed by using Analysis of Variance and following by Honestly Significant Difference (HSD) post hoc test. Here, we identified that banana stem extract contain different type of active substance such as tannin, saponin, and alkaloid. Banana stem extract significantly affected the oocysts sporulation included the amount of sporulatedoocysts (P<0.01), unsporulatedoocysts (P<0.01), and transformed oocysts (P<0.01). In conclusion banana stem could inhibit the development of Eimeria stiedaioocysts on in vitroexperiment. HSD test showed that the optimum potential efficacy of banana stem toinhibit sporulation was at 4% and 8% concentration during three days incubation.